Ethylene Biosynthesis, Signaling, and Crosstalk with Other Hormones in Rice. Issue 8 (13th August 2019) - Zhou, Yang; Xiong, Qing; Yin, Cui‐Cui; Ma, Biao; Chen, Shou‐Yi; Zhang, Jin‐Song
Abstract: Ethylene is a multifunctional hormone involved in regulating plant development, conferring adaptive growth, and responding to biotic/abiotic stresses. Rice is a monocotyledonous crop and usually grows in water environments with some unique features. Here, ethylene biosynthesis, signaling, and interaction with other hormones in rice are summarized and discussed in comparison to those from Arabidopsis and/or other plants. Ethylene biosynthesis in rice responds to internal developmental signals and external stimuli such as grain filling, leaf senescence, darkness, mechanical resistance, hypoxia, chill, salt stress, and metal ions. Gene expression regulation in ethylene biosynthesis pathway shows time and spatial specificity. Through mutant analysis and homologue analysis, an ethylene signaling pathway is proposed in rice, and conserved components/mechanisms as well as new components/mechanisms are identified. Ethylene widely interacts with other hormones in rice by synergy or antagonism. Normally, auxin and gibberellin are synergistic with ethylene to regulate growth, while abscisic acid is antagonistic to ethylene in reproductive growth and various stress response. Ethylene diminishes jasmonic acid–inhibited elongation growth, but synergistically promotes leaf senescence. All these studies provide novel insights into the ethylene biology in rice and other crops, and may facilitate breeding for cultivars with better agronomic traits. Abstract : Several aspects of rice ethylene biology are covered. Specific biosynthesis regulation, elegant signaling pathway, and networked hormone crosstalk provide a multilevel control to ethylene response during growth of rice. The unique features of rice disclose novel components and mechanisms in ethylene signaling. These findings provide insights into improvement of cultivars for better agronomic traits and adaptation to environments.